Engineering properties of fine grained soils of Kathmandu Valley, Nepal - Katel, T. P.; Upreti, B. N.; Pokharel, G. S. (Journal of Nepal Geological Society, 1996)
This paper primarily deals with the distribution, and engineering and geotechnical properties of fine grained soils in the Kathmandu Valley. Not much studies have been done on these soils in the past except at some engineering construction sites such as bridges and heavy buildings. Very little data are available on the engineering and geotechnical properties of soils of the valley (IOE, 1983a, 1983b, 1986a, 1986b, 1986c; Koirala et al., 1993; Sadaula, 1993; Shakya, 1987; Soil Test, 1990a, 1990b). The authors conducted detailed laboratory studies on the soils of the Thapathali and Ratnapark areas in the central part of the Kathmandu Valley and the results are presented and discussed. An attempt is also made to broadly evaluate the soil conditions of the valley based on the available data from previous studies conducted by various agencies. The soils of the Kathmandu Valley are mainly produced by weathering of rocks within its watershed boundary. They are in most part lacustrine and fluvial in origin and composed of clayey, silty, sandy and gravely sediments. The maximum thickness of the sediment is found in the central part (550 m at Bhrikutimandap) and southern part (>457m at Harishidhi) of the valley. The engineering properties, basically the index properties such as grain size, natural moisture content specific gravity, Atterberg limits; and the mechanical properties such as penetration resistance, cohesion, unconfined compressive strength, compressibility as well as angle of shearing resistance of fine grained soils were determined and found to vary considerably both in horizontal and vertical directions. The bearing capacity and settlement values of the soils were also determined. It is commonly found that most of the buildings in the Kathmandu Valley are founded on isolated or strip types of foundations and the foundation depth is between 1 and 1.5 m. The study of soil properties of the Kathmandu Valley indicates that the heavy loaded structures should be founded on either raft, mat or pile types of foundation.